Globalization and development Economic and socio-cultural perspectives from emerging markets - Nezameddin Faghih; editor (Switzerland Springer, 2019)
This book presents economic and socio-cultural perspectives on globalization from emerging markets. It explores the links between globalization and development, and reveals the dynamics, strengths and weaknesses, trends in and implications of globalization in emerging market economies. Gathering papers by leading experts in the field, it shares essential insights into the history and status quo of globalization processes and structures; identifies the opportunities provided by and risks posed by globalization; and sheds light on the way to global peace. The topics addressed range from globalization development within the Group of Twenty (G20), populist events such as (3z(BBrexit(3y (Bas a form of historical irony, and a zeitgeist analysis of the globalization spirit; to the evolution of higher education and public administrative systems under the weight of globalization; not to mention emerging topics such as the informal economy and new rules for fleecing the South in the newly globalized trade system.s
Keywords: Globalization; Developing countries; Economic development; Economic development projects--Finance